The influence of hand position on scapular kinematics in push-ups: comparing athletes with chronic shoulder pain and healthy controls - Sajjad Abdollahi; Rahman Sheikhhoseini; Mohammad Salsali; Hashem Piri; Julie A. Hides (Journal of Orthopaedic Surgery and Research)
Abstract Background Scapulothoracic motion during arm elevation involves scapular posterior tilt (PT), upward rotation (UR), and external rotation (ER). Abnormal scapular kinematics are common in people with chronic shoulder pain, potentially exacerbating symptoms and impairing function. Push-ups, a common exercise for shoulder rehabilitation, may influence scapular motion but have not been extensively studied in this context. Thus, this study aimed to investigate the effect of hand position on scapular kinematics during a push-up exercise in athletes with and without chronic shoulder pain (CSP). Methods Twenty-four male overhead athletes were allocated into two groups: CSP (n = 12) and Control (CON; n = 12). Scapular kinematics in three planes (PT, UR, and ER) were measured using a Vicon motion capture system during push-ups in three hand positions (internal rotation, IR; neutral rotation, NR; and external rotation, ER). Measurements were taken in the concentric phase of the push-up. Statistical analyses using repeated-measures ANOVA assessed the effects of hand position and elbow extension on scapular kinematics between the two groups. Results For PT of the scapula, in the IR hand position, participants from both the CON and CSP groups showed similar decreases (CON group = from 25.74° to -16.10°; P < 0.001). In the NR hand condition, the CON group decreased PT from 16.12° to -15.98° (P < 0.001), but there was no significant change in the CSP group. In the ER hand condition, for the CON group, PT decreased from 18.63° to -9.38° (P < 0.026), with no significant change observed in the CSP group. For UR of the scapula, the CON group showed significant decreases in the IR hand condition (from 15.37° to -2.28°; P < 0.019), while the CSP showed minimal changes. In the IR hand condition, the ER of the scapula increased from 20.44° to 25.13° (P < 0.003) in the CON group. At the same time, the CSP showed smaller changes. In the NR hand condition, ER of the scapula in the CON group decreased from 24.79° to 9.38° (P < 0.001), with no significant change observed in the CSP group. Conclusion Scapular kinematics (UR, PT, and ER) differed significantly across hand rotation conditions and groups. The CON group exhibited more pronounced changes in these kinematic measures, while the CSP group showed limited variation. This may indicate an association between chronic pain and movement restriction. These findings emphasize the need for targeted rehabilitation strategies that consider these kinematic differences.